Peta kekerasan : pengalaman perempuan Indonesia. - Komnas Perempuan (Organization : Indonesia) (Jakarta : Komnas Perempuan, 2002)
Violence against women in Indonesia.
"Daftar lembaga yang menangani isu kekerasan terhadap perempuan": p. 322-344.
Includes bibliographical references (p. 290-297) and index.
Keywords: Women -- Crimes against -- Indonesia; Women -- Violence against -- Indonesia; Abused women -- Indonesia; Violent crimes -- Indonesia